Brand Identity UD Bakriy Furniture Sebagai Upaya Meningkatkan Brand Awareness - Dian Dwi Saputra; Yogi Widya Saka Warsaa; Handry Rochmad Dwi Happy (Jurnal Desain Komunikasi Visual Asia, 2023)
Having no visual identity makes UD. Bakriy Furniture is experiencing difficulties in hooking up new customers. That's not all the UD factor. Bakriy Furniture experienced difficulties in hooking up new customers, along with several other factors, namely, the change in the spelling of the name as well as the company's vision and mission. Subsequent changes in the ownership structure include innovations in new product variants, expansion of products and services, updating of furniture styles and designs as well as variants following the wishes and attractiveness of consumers. Differentiate from several regional competitors, especially the city of Pasuruan. The research method used is observation, namely coming directly to the location to conduct interviews with Muchammad Al Hamid as the owner of UD. Bakriy Furniture and Haidar Al Hamid, representatives from UD. Bakriy Furniture., supported by conducting literature studies sourced from books. The rebranding process starts from creating a concept, making thumbnails and then roughlayout. The test results using the questionnaire method in this study showed that out of 10 respondents agreed with the visual identity of UD. Bakriy Furniture which is able to reflect the company's identity.